THE WATER CONTENT TEST ON UNREGISTERED BRAND SLIMMING JAMU CIRCULATION IN CIMAHI CITY - Ellen Stephanie Rumaseuw; Ancilla Dinda Kartika Candra (Jurnal Kesehatan, 2022)
Based on rules of National Agency of Drug and Food Control No. 32 of 2019 concerning the Safety and Quality Requirements of Traditional Medicines, it is stated that every traditional medicine must have a water content value of 10%. Excessive water content in a product will result in a decrease in the quality of traditional medicinal preparations. This study was conducted with the aim of determine the percentage of the water content of unregistered branded slimming herbal products circulating in Cimahi City by the provisions of water content requirements based on BPOM. This research is quantitative research using experimental methods. Determination of water content in this study using the gravimetric method, with the heating method at a temperature of 105°C at a certain time. Based on the results of the study, it was obtained that the average value of water content in the six herbal medicine samples, namely samples A, B, C, D, E, F, respectively, was 10.5%; 13.55%; 10.65%; 11.58%; 11.01% and 8.48%. So that the value of the water content of branded slimming herbs is not registered in Cimahi City, only one of the six samples studied has met the requirements set by BPOM is F sample.